Effect of The Inclusion of Butterfly Pea (Clitoria ternatea) and Green Sea Weed (Ulva lactuca) in The Complete Feed on The Concentration of Blood Metabolites of Male Kacang Goats - I Gusti Ngurah Jelantik; Wigberta N. Mano; T. T. Nikolaus (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2022)
This experiment aimed to investigate the effect of including Clitoria ternatea and Ulva lactuca in the complete feed on the concentration of blood metabolites of male kacang goats. Four male kacang goats were involved in this experiment arranged following a Latin Square Design with 4 treatments and 4 periods as replication. The treatments were R0= native grass hay 60%+concentrate 40%, R1= native grass hay 30%+concentrate 40%+ Clitoria ternatea 30%, R2= native grass hay 30%+concentrate 40%+ Clitoria ternatea 15%+ Ulva lactuca 15% and R3= native grass hay 30%+ concentrate 40%+Ulva lactuca 30%. Data were analyzed using analysis of variance (ANOVA) and followed by the Duncan Multiple Range Test when significant differences were found. The results showed that feeding a complete feed containing Clitoria ternatea and Ulva lactuca did not significantly (P>0,05) affect the concentration of urea, glucose and plasm total protein in the blood of male kacang goats. Therefore, it can be concluded the inclusion of Clitoria ternatea and Ulva lactuca has no effect on the concentration of blood metabolites in male kacang goats.